الكوميديا في مسرح الطفل (أهميتها وأشكالها) - حبيب حبيب ظاهر (lark, 2019)
Abstract Search: Comedy in children’s theater (its importance and forms) Proceeding from that theater-oriented child must enter joy to the hearts of children by providing experience includes fun and useful. The research aims to identify the importance and forms of comedy in the children’s theater shows. The theoretical framework of: Section I: read in the philosophy of comedy / laughter: be dealt with proposals a number of philosophers, thinkers and scientists to comedy and laughter, notably (Henri Bergson) who sees: that of funny social impact significance socially - that is not funny is human - the thrill of laughter Even in the theater tinged hidden idea - that comedy is closer to real-life tragedy. And display the topic sorting includes four forms of comedy are: 1. Personal comedy. 2. behavioral comedy. 3. comedy situations. 4. Comedy humoristic. The second topic: saved through him to the importance of comedy in children’s theater , and comedy shows that reduced the distance between the child and the theatrical presentation : for two reasons : (a) because it is closer to real life . (B) as they enter joy and pleasure to the child ’s world. The existence of comedy theater in the child makes the child a positive recipient. Find the measures have been described and analysis of a play: Cinderella and birds of paradise. Preparation: Mansour Al Noman, Director: Faleh Al Fayez, provide: Doha band play. The research found a number of conclusions, including: embodied Comedy behavior naughty for the mother and her two daughters and backs moral level low when the mother her two daughters affect unlawfully Cinderella, and show the girls behavior stupid in a lot of behaviors, use and supply means shun three times in a personal album, already dramatic in The research sample was not based on a comic theme, act as focused on finding the wife of the Emir, to the joy of the display ends with the announcement of marriage that everyone is happy. Function personal attitudes comedy and comedy is a function of recreational to add to the fun and the purpose of easing tension and stress caused by the dramatic act. Search of the most important conclusions: that the comedy in children’s theater and a way to establish a certain idea of ​​dialogue is important, and to highlight the behavior of specific positive or negative. Comedy and help the child to relax , and contribute to unload shipments tension has , that the presence of comedy in a child -oriented presentation lends the character of diversity on the show , prompting boredom child for the show, and help him to participate in the show. And that the dominant form of comedy in children’s theater offers is a situation comedy and personal.